2022
DOI: 10.1097/gox.0000000000004142
|View full text |Cite
|
Sign up to set email alerts
|

Operation-related Musculoskeletal Injuries among United States Surgeons: A Gender-stratified National Survey

Abstract: Background: Operation-related musculoskeletal injury (ORMI) among surgeons is a well-described phenomenon. Our study aimed to determine the prevalence of self-reported ORMI among surgeons of various subspecialties and preliminarily investigate the role of gender. Methods: An anonymous survey, querying information pertinent to ORMIs, was distributed online through the American College of Surgeons community membership forum. Nonparametric univariate analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…In a survey of American College of Surgeons members, a higher rate of occupational-related musculoskeletal injuries was found among female versus male surgeons. 10 Similarly, among general surgeons, women were found to have a 5-fold odds of physical complaints when using laparoscopic devices, findings which were replicated in orthopedic surgeons. [17][18][19] In otolaryngology, an ergonomically high-risk field, no prior work had specifically examined the surgical ergonomic hazards experienced by females.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a survey of American College of Surgeons members, a higher rate of occupational-related musculoskeletal injuries was found among female versus male surgeons. 10 Similarly, among general surgeons, women were found to have a 5-fold odds of physical complaints when using laparoscopic devices, findings which were replicated in orthopedic surgeons. [17][18][19] In otolaryngology, an ergonomically high-risk field, no prior work had specifically examined the surgical ergonomic hazards experienced by females.…”
Section: Discussionmentioning
confidence: 90%
“…While all body sizes present unique ergonomic challenges, recent studies have shown higher rates of ergonomic difficulties and work-related musculoskeletal pain in women. 4,[10][11][12] Challenges with ergonomics and concerns about the physical demands of surgical fields have been shown to affect surgeon recruitment, a finding which likely extends to surgeon retainment and advancement as well. 13 Given this, attention to the ergonomics of female otolaryngologists is important for continued female otolaryngologist recruitment and advancement.…”
mentioning
confidence: 99%
“…26 A majority of surgeons report exercise alleviates this pain and discomfort. 36 It is uncertain how much provided athletic resources can improve posture and strength or whether residents have sufficient time for consistent exercise. As well, these resources are insufficient to treat musculoskeletal injury once it has occurred.…”
Section: Address Physical Dimensions Of Well-beingmentioning
confidence: 99%
“…Physical health is an emerging concern of resident wellness, as upwards of 60% of plastic surgeons report experiencing procedural-related musculoskeletal injury. 36,37 Alarmingly, up to 97% have reported experiencing musculoskeletal pain during training. 26 A majority of surgeons report exercise alleviates this pain and discomfort.…”
Section: Address Physical Dimensions Of Well-beingmentioning
confidence: 99%
“…Orthopedic surgeons' rate of shoulder dysfunction might differ due to various factors, such as age, surgical specialization, volume and type of procedures performed, and ergonomic practices [1]. Due to the physically demanding nature of their profession, which frequently entails long hours of standing, wearing heavy lead aprons during fluoroscopy, and performing repeated activities in uncomfortable postures, orthopedic surgeons are susceptible to acquiring musculoskeletal issues, including shoulder discomfort [2].…”
Section: Introductionmentioning
confidence: 99%